SIGNALL: Developing online and blended deaf studies course content across EU borders - LEESON, LORRAINE (My University, 2009)
This paper presents interim outcomes of a European Commission funded project which brings together industry, academics and practitioners in an innovative project to create an international forum of learning. SIGNALL 2 builds on the successes of SIGNALL 1 (both Leonardo da Vinci funded projects). The core content for the `Perspectives on Deafness? course was created by the Centre for Deaf Studies (CDS) at Trinity College Dublin. CDS has actively engaged in the development of digital learning assets to support traditional delivery of programmes, and are actively engaged in the development of blended learning diplomas and degrees. European perspectives are added, allowing for the exploration of shared ? and differing- experiences of Deafhood (Ladd 2003) across Europe as well as notions of d/Deafness as a medical, social, cultural, and historical construct. Human rights perspectives are also explored in this wide reaching course. This paper outlines the background to the development of this course, outlining rationale, content, creation of multimodal digital materials in nine languages - 4 spoken and 5 signed languages, the nature of international involvement and the challenges to creating a repository of digital courseware that will be accessible and relevant to Deaf and hearing students and employers across the European Union, and beyond.
ACCEPTED
Keywords: E-learning, Deaf Studies, Signed Languages, Accessibility, European collaboration